(untitled) (Contemporary Journal of Social Science Review, 2026)
The growing integration of digital technologies into educational environments has increased concerns regarding online safety, ethical technology use, and responsible digital participation among school learners. This qualitative study explored middle school teachers’ perspectives regarding digital citizenship and online safety practices in Karachi schools. The study investigated ethical online behavior, cyber safety awareness, responsible technology use, and challenges associated with maintaining safe digital learning environments. A qualitative descriptive research design was employed, and data were collected from ten middle school teachers through semi-structured interviews using purposive sampling. Thematic analysis based on Braun and Clarke’s framework was used to analyze the data. The findings revealed that teachers considered respectful communication, cybersecurity awareness, digital responsibility, and ethical online behavior essential components of digital citizenship education. Participants also identified cyberbullying, phishing attacks, misinformation, plagiarism, privacy violations, and harmful online content as major digital risks. Furthermore, insufficient parental monitoring, inconsistent institutional policies, and limited teacher training were identified as significant challenges. The study concludes that digital citizenship education is essential for promoting safe, ethical, and responsible participation in technology-supported learning environments.